Metal surface treatment composition and method for producing the same

The metal surface treatment composition, utilizing a three-phase emulsification method with an aqueous organic polymer compound and silane coupling agent, addresses the issues of storage stability and corrosion resistance, achieving superior performance without conventional surfactants.

JP2025069481AInactive Publication Date: 2025-05-01KANAGAWA UNIVERSITY +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022050767
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-25
Publication Date
2025-05-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing metal surface treatment compositions, particularly those containing organic resin and silane coupling agents, often suffer from insufficient storage stability and compromised corrosion resistance due to the use of surfactants, which may not adequately improve storage stability and can decrease chemical resistance.

Method used

A metal surface treatment composition is developed using a three-phase emulsification method, incorporating an aqueous organic polymer compound and a silane coupling agent, without the need for conventional surfactants. This composition employs an emulsifier containing an amphiphile that forms a closed endoplasmic reticulum or a polycondensation polymer with hydroxyl groups, significantly enhancing storage stability and corrosion prevention properties.

Benefits of technology

The composition achieves excellent storage stability and corrosion prevention, with improved curability and solvent resistance, resulting in a highly uniform coating film that enhances the metal surface treatment process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069481000001
    Figure 2025069481000001
  • Figure 2025069481000002
    Figure 2025069481000002
  • Figure 2025069481000003
    Figure 2025069481000003
Patent Text Reader

Abstract

To provide a metal surface treatment composition capable of forming a film having excellent storage stability and corrosion resistance as well as excellent curability, and a method for producing the metal surface treatment composition.SOLUTION: The present invention provides a metal surface treatment composition that includes: an aqueous organic polymer compound (A); an emulsifier (B) including at least one substance selected from amphiphilic substances forming closed vesicles and polycondensation polymers having a hydroxyl group; and a silane coupling agent (C). The present invention provides a method for producing the metal surface treatment composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a metal surface treatment composition and a method for producing the metal surface treatment composition. [Background technology]

[0002] Generally, techniques for providing excellent adhesion to metal material surfaces and corrosion resistance to the metal material surfaces include a chromate treatment using a treatment liquid containing chromic acid, dichromic acid or a salt thereof as a main component, a phosphate treatment, a treatment mainly using inorganic components, a treatment using a silane coupling agent, an organic resin film treatment, and the like, which are known and in practical use.

[0003] As a technique for performing treatment with an inorganic component, Patent Document 1 lists a metal surface treatment agent containing a vanadium compound and a metal compound containing at least one metal selected from zirconium, titanium, molybdenum, tungsten, manganese, and cerium.

[0004] As a technique using a silane coupling agent, a surface treatment agent containing an organofunctional silane and a polysiloxane is taught. Patent Document 2 discloses a method for forming a siloxane film having improved adhesion to a substrate from an organofunctional silane and a polysiloxane.

[0005] Patent Document 3 discloses a technique for applying an organic resin film treatment, which uses a surface treatment agent containing a specific resin compound (A), a cationic urethane resin (B) having at least one cationic functional group selected from primary to tertiary amino groups and a quaternary ammonium base, one or more silane coupling agents (C) having a specific reactive functional group, and a specific acid compound (E), and the contents of the cationic urethane resin (B) and the silane coupling agent (C) are within specified ranges. The surface treatment agent provides a non-chrome-based steel sheet with excellent corrosion resistance, fingerprint resistance, blackening resistance and paint adhesion.

[0006] Meanwhile, a three-phase emulsification method is known as an emulsification method for aqueous compositions. The three-phase emulsification method is completely different from the surfactants used in conventional emulsification methods, and is expected to be an emulsification method that utilizes the physical action force (van der Waals attractive force) of soft hydrophilic nanoparticles (see Patent Documents 4 to 7, etc.). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2002-30460 A [Patent Document 2] Japanese Patent Application Publication No. 11-43647 [Patent Document 3] JP 2003-105562 A [Patent Document 4] JP 2006-239666 A [Patent Document 5] JP 2013-216607 A [Patent Document 6] International Publication No. 2018 / 135108 [Patent Document 7] JP 2019-26708 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, in the above-mentioned conventional techniques, the techniques for carrying out organic resin film treatment, particularly the surface treatment agent having an organic resin and a silane coupling agent as components as in Patent Document 3, may have insufficient storage stability. Also, a surfactant may be used in combination to improve storage stability, but the improvement effect is insufficient, and the coating film obtained becomes highly hydrophilic due to the influence of the surfactant, which may result in reduced corrosion resistance and chemical resistance (acid, alkali).

[0009] An object of the present invention is to provide a metal surface treatment composition capable of forming a film having excellent storage stability and corrosion resistance and also excellent curability, and a method for producing said metal surface treatment composition. [Means for solving the problem]

[0010] The present inventors have studied a metal surface treatment composition comprising an aqueous organic polymer compound and a silane coupling agent. As a result, they have found that by applying a three-phase emulsification method to the production of a metal surface treatment composition, the storage stability of the metal surface treatment composition comprising an organic resin and a silane coupling agent is significantly improved without the need for a conventional surfactant, and the formed film is excellent in corrosion resistance and curability, leading to the completion of the present invention.

[0011] That is, the present invention is characterized by the following items 1 to 12. Section 1. A metal surface treatment composition comprising: an aqueous organic polymer compound (A); an emulsifier (B) containing at least one selected from an amphiphilic substance that forms closed vesicles and a polycondensation polymer having a hydroxyl group; and a silane coupling agent (C). Section 2. 2. A metal surface treatment composition according to item 1, wherein the water-based organic polymer compound (A) has at least one group selected from a nonionic hydrophilic group and a cationic hydrophilic group. Section 3. 3. The metal surface treatment composition according to item 1 or 2, wherein the water-based organic polymer compound (A) is at least one selected from the group consisting of acrylic resins, polyurethane resins and epoxy resins. Section 4. 4. The metal surface treatment composition according to any one of items 1 to 3, wherein the amphiphilic substance is polyoxyethylene hydrogenated castor oil. Section 5. 5. The metal surface treatment composition according to any one of items 1 to 4, wherein the silane coupling agent (C) is at least one selected from the group consisting of epoxy group-containing silane coupling agents and amino group-containing silane coupling agents. Section 6. 6. The metal surface treatment composition according to any one of items 1 to 5, wherein the water-based organic polymer compound (A) is emulsion-stabilized by the emulsifier (B). Section 7. A method for producing the metal surface treatment composition according to any one of items 1 to 6, A method for producing a metal surface treatment composition, comprising a step of mixing a composition containing an aqueous organic polymer compound (A) with an emulsifier (B) containing at least one selected from an amphiphilic substance that forms closed vesicles and a polycondensation polymer having a hydroxyl group. Section 8. A method for producing the metal surface treatment composition according to any one of items 1 to 6, A method for producing a metal surface treatment composition, comprising the step of adding, under stirring, an emulsifier (B) containing at least one selected from an amphiphilic substance that forms closed vesicles and a polycondensation polymer having a hydroxyl group to a composition containing an aqueous organic polymer compound (A). Section 9. A method for producing the metal surface treatment composition according to any one of items 1 to 6, A step of adding an emulsifier (B) containing at least one selected from an amphiphilic substance that forms closed vesicles and a polycondensation polymer having a hydroxyl group to water under stirring to obtain a water dilution of the emulsifier (B); A method for producing a metal surface treatment composition, comprising the step of mixing a composition containing a water-based organic polymer compound (A) with the water dilution. Section 10. A method for producing the metal surface treatment composition according to any one of items 1 to 6, A step of adding an emulsifier (B) containing at least one selected from an amphiphilic substance that forms closed vesicles and a polycondensation polymer having a hydroxyl group to water under stirring to obtain a water dilution of the emulsifier (B); A method for producing a metal surface treatment composition, comprising the step of adding the water dilution under stirring to a composition containing a water-based organic polymer compound (A). Section 11. A method for treating a metal surface, comprising applying the metal surface treatment composition according to any one of items 1 to 6 onto a metal substrate and drying the composition. Section 12. 7. A surface-treated metal sheet obtained by subjecting a surface of a metal substrate to a surface treatment with the metal surface treatment composition according to any one of items 1 to 6. Effect of the Invention

[0012] According to the present invention, it is possible to provide a novel metal surface treatment composition which makes it possible to achieve both storage stability and corrosion resistance of the coating film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The metal surface treatment composition of the present invention is a composition comprising an aqueous organic polymer compound (A), an emulsifier (B) containing at least one selected from an amphiphilic substance that forms closed vesicles and a polycondensation polymer having a hydroxyl group, and a silane coupling agent (C). The metal surface treatment composition of the present invention has excellent storage stability due to the inclusion of the above three components. The reason why the storage stability of the metal surface treatment composition of the present invention is remarkably improved is not necessarily clear, but it is believed that the specific emulsifier (B) is firmly adsorbed to the aqueous organic polymer compound, and the dispersion state of the resin particles is remarkably stabilized, resulting in the suppression of the interaction between the resin particles and the silane coupling agent or its hydrolyzate. The resin particles stabilized with the emulsifier (B) also improve the stability during the process of heating and drying the metal surface treatment composition to form a film, contributing to the expression of excellent coating film performance. In other words, it is believed that abnormal precipitation of the treatment agent components during the film formation process is suppressed, resulting in a highly uniform coating film, which improves corrosion prevention and curability (solvent rubbing resistance, etc.).

[0014] <Aqueous organic polymer compound (A)> The aqueous organic polymer compound, which is the component (A) of the metal surface treatment composition of the present invention, can be one having a water-soluble, water-dispersible or emulsifiable form. The organic polymer compound can be dissolved, dispersed or emulsified in water by a conventionally known method. Specifically, the organic polymer compound can be one containing a functional group (e.g., at least one of a hydroxyl group, a carboxyl group, an amino (imino) group, a sulfide group, a phosphine group, etc.) that can be dissolved or dispersed in water by itself, and one in which a part or all of the functional groups are neutralized with an amine compound such as ethanolamine or triethylamine in the case of an acidic resin (such as a carboxyl group-containing resin), an aqueous ammonia, or an alkali metal hydroxide such as lithium hydroxide, sodium hydroxide, or potassium hydroxide, or one in which a fatty acid such as acetic acid or lactic acid, or a mineral acid such as phosphoric acid in the case of a basic resin (such as an amino group-containing resin), can be neutralized.

[0015] The metal surface treatment composition of the present invention may be adjusted to an acidic pH range or may contain an acidic rust inhibitor in order to promote hydrolysis of the alkoxy group of the silane coupling agent (C). Therefore, the aqueous organic polymer compound is preferably stable at a pH of 7 or less. The functional group contained in the aqueous organic polymer compound is preferably a nonionic hydrophilic group and / or a cationic hydrophilic group.

[0016] Examples of such aqueous organic polymer compounds (A) include epoxy resins, phenol resins, acrylic resins, polyurethane resins, olefin-carboxylic acid resins, nylon resins, resins having a polyoxyalkylene chain, polyvinyl alcohol resins, polyglycerin, carboxymethyl cellulose, hydroxymethyl cellulose, and hydroxyethyl cellulose.

[0017] As the epoxy resin, cationic epoxy resins obtained by adding amine to epoxy resins; modified epoxy resins such as acrylic modified and urethane modified, etc., can be suitably used. Examples of cationic epoxy resins include adducts of epoxy compounds with primary mono- or polyamines, secondary mono- or polyamines, mixed primary and secondary polyamines, etc. (see, for example, U.S. Pat. No. 3,984,299); adducts of epoxy compounds with secondary mono- or polyamines having a ketiminated primary amino group (see, for example, U.S. Pat. No. 4,017,438); and etherification reaction products of epoxy compounds with hydroxyl compounds having a ketiminated primary amino group (see, for example, JP-A-59-43013).

[0018] The epoxy compound is suitable for use as the epoxy compound having a number average molecular weight in the range of 400 to 4,000, particularly 800 to 2,000, and an epoxy equivalent in the range of 190 to 2,000, particularly 400 to 1,000. Such an epoxy compound can be obtained, for example, by reacting a polyphenol compound with epichlorohydrin. Examples of the polyphenol compound include bis(4-hydroxyphenyl)-2,2-propane, 4,4-dihydroxybenzophenone, bis(4-hydroxyphenyl)-1,1-ethane, bis(4-hydroxyphenyl)-1,1-isobutane, bis(4-hydroxy-tert-butylphenyl)-2,2-propane, bis(2-hydroxynaphthyl)methane, 1,5-dihydroxynaphthalene, bis(2,4-dihydroxyphenyl)methane, tetra(4-hydroxyphenyl)-1,1,2,2-ethane, 4,4-dihydroxydiphenylsulfone, phenol novolac, and cresol novolac. These epoxy compounds can be used alone or in combination of two or more.

[0019] As the phenolic resin, a water-soluble polymeric compound obtained by heating a phenolic component and a formaldehyde in the presence of a reaction catalyst to add and condense can be suitably used. As the phenolic component as a starting material, a bifunctional phenolic compound, a trifunctional phenolic compound, a tetrafunctional or higher phenolic compound, etc. can be used. For example, bifunctional phenolic compounds include o-cresol, p-cresol, p-tert-butylphenol, p-ethylphenol, 2,3-xylenol, 2,5-xylenol, etc.; trifunctional phenolic compounds include phenol, m-cresol, m-ethylphenol, 3,5-xylenol, m-methoxyphenol, etc.; and tetrafunctional phenolic compounds include bisphenol A, bisphenol F, etc. These phenolic compounds can be used alone or in a mixture of two or more.

[0020] Examples of the acrylic resin include homopolymers or copolymers of monomers having a hydrophilic group such as a carboxyl group, an amino group, or a hydroxyl group, and copolymers of a monomer having a hydrophilic group and another copolymerizable monomer, etc. These are resins obtained by emulsion polymerization, suspension polymerization, or solution polymerization and, if necessary, neutralizing or water-based resins, or by modifying such resins.

[0021] Examples of the carboxyl group-containing monomer include acrylic acid, methacrylic acid, maleic acid, maleic anhydride, crotonic acid, and itaconic acid.

[0022] Examples of the nitrogen-containing monomer include nitrogen-containing alkyl (meth)acrylates such as N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, and Nt-butylaminoethyl (meth)acrylate; polymerizable amides such as acrylamide, methacrylamide, N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-methylol (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-dimethylaminopropyl (meth)acrylamide, and N,N-dimethylaminoethyl (meth)acrylamide; aromatic nitrogen-containing monomers such as 2-vinylpyridine, 1-vinyl-2-pyrrolidone, and 4-vinylpyridine; and allylamine.

[0023] Examples of the hydroxyl group-containing monomer include monoesters of polyhydric alcohols and acrylic acid or methacrylic acid, such as 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, 2,3-dihydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and polyethylene glycol mono(meth)acrylate; and compounds obtained by ring-opening polymerization of the monoesters of the above-mentioned polyhydric alcohols and acrylic acid or methacrylic acid with ε-caprolactone.

[0024] Examples of other monomers include alkyl (meth)acrylates having 1 to 24 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl acrylate, n-octyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, octadecyl (meth)acrylate, and isostearyl (meth)acrylate; styrene, and vinyl acetate.

[0025] In the present invention, "(meth)acrylate" means acrylate or methacrylate, and "(meth)acrylic" means acrylic or methacrylic, respectively.

[0026] As the polyurethane-based resin, a polyurethane consisting of a polyol such as polyester polyol or polyether polyol and a diisocyanate can be preferably chain-extended in the presence of a chain extender, which is a low molecular weight compound having two or more active hydrogens such as a diol or diamine, and stably dispersed or dissolved in water, and a wide variety of known resins can be used (see, for example, JP-B-42-24192, JP-B-42-24194, JP-B-42-5118, JP-B-49-986, JP-B-49-33104, JP-B-5027, and JP-B-53-29175).

[0027] As a method for stably dispersing or dissolving the polyurethane resin in water, for example, the following method can be used. (1) A method in which ionic groups such as hydroxyl groups, amino groups, and carboxyl groups are introduced into the side chains or ends of a polyurethane polymer to impart hydrophilicity, thereby dispersing or dissolving the polymer in water through self-emulsification. (2) A method in which a polyurethane polymer in which the reaction has been completed or a polyurethane polymer in which the terminal isocyanate groups have been blocked with a blocking agent such as oxime, alcohol, phenol, mercaptan, amine, or sodium bisulfite is forcibly dispersed in water using an emulsifier and mechanical shearing force. A method in which a polyurethane polymer having terminal isocyanate groups is mixed with water / emulsifier / chain extender and mechanical shearing force is used to simultaneously disperse and polymerize the polymer. (3) A method in which a water-soluble polyol such as polyethylene glycol is used as the main raw material polyol for polyurethane, and the polyurethane is dispersed or dissolved in water to produce a water-soluble polyurethane.

[0028] The above-mentioned polyurethane resin is not limited to being dispersed or dissolved by a single method, and a mixture obtained by each method may also be used.

[0029] Examples of diisocyanates that can be used in the synthesis of the polyurethane resin include aromatic, alicyclic and aliphatic diisocyanates. Specific examples of the diisocyanates include hexamethylene diisocyanate, tetramethylene diisocyanate, 3,3'-dimethoxy-4,4'-biphenylene diisocyanate, p-xylylene diisocyanate, m-xylylene diisocyanate, 1,3-(diisocyanatomethyl)cyclohexanone, 1,4-(diisocyanatomethyl)cyclohexanone, 4,4 Examples of suitable isocyanates include 1,4-diisocyanatocyclohexanone, 4,4'-methylenebis(cyclohexyl isocyanate), isophorone diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, p-phenylene diisocyanate, diphenylmethane diisocyanate, m-phenylene diisocyanate, 2,4-naphthalene diisocyanate, 3,3'-dimethyl-4,4'-biphenylene diisocyanate, 4,4'-biphenylene diisocyanate, etc. Among these, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate are particularly preferred.

[0030] Commercially available examples of the polyurethane resin include Hydran HW-330, HW-340, and HW-350 (product names, all manufactured by DIC Corporation), Superflex 100, 150, and F-3438D (product names, all manufactured by Daiichi Kogyo Seiyaku Co., Ltd.).

[0031] The polyvinyl alcohol resin is preferably a polyvinyl alcohol having a saponification degree of 87% or more, and particularly preferably a so-called fully saponified polyvinyl alcohol having a saponification degree of 98% or more. The number average molecular weight of the polyvinyl alcohol resin is preferably within the range of 3,000 to 100,000.

[0032] As the resin having the polyoxyalkylene chain, those having a polyoxyethylene chain or a polyoxypropylene chain can be suitably used, and examples thereof include polyethylene glycol, polypropylene glycol, and blocked polyoxyalkylene glycol in which the polyoxyethylene chain and the polyoxypropylene chain are bonded in the form of blocks.

[0033] As the olefin-carboxylic acid-based resin, at least one water-dispersible or water-soluble resin selected from the following two types can be suitably used: (1) a copolymer of an olefin such as ethylene or propylene with a polymerizable unsaturated carboxylic acid; and (2) a resin obtained by adding a polymerizable unsaturated compound to a dispersion of the copolymer, emulsion polymerizing the copolymer, and then intraparticle-crosslinking the copolymer.

[0034] The copolymer (1) is a copolymer of an olefin and one or more unsaturated carboxylic acids such as (meth)acrylic acid, maleic acid, etc. In the copolymer (1), the content of the unsaturated carboxylic acid is suitably within the range of 3 to 60% by mass, preferably 5 to 40% by mass, and the copolymer can be dispersed in water by neutralizing the acid groups in the copolymer with a basic substance.

[0035] The resin (2) is a crosslinked resin obtained by emulsion polymerization of an aqueous dispersion of the copolymer (1) by adding a polymerizable unsaturated compound, and then crosslinking the polymerizable unsaturated compound within the particles. Examples of the polymerizable unsaturated compound include the vinyl monomers listed in the description of the water-dispersible or water-soluble acrylic resin, and one or more of these may be appropriately selected and used.

[0036] The above-mentioned aqueous organic polymer compound is dispersed or dissolved in water. A known method is adopted as a method for dispersing or dissolving in water. For example, the aqueous organic polymer compound is produced by emulsion polymerization using a surfactant, a surfactant is mixed with the aqueous organic polymer compound and dispersed / dissolved in an aqueous medium, when the aqueous organic polymer compound has an ionic functional group such as a carboxyl group or an amino group in the molecule, the ionic functional group is neutralized with a neutralizing agent, and then dispersed / dissolved in water, or a combination of the above methods.

[0037] The water-based organic polymer compound (A) may be prepared by manufacturing, or a commercially available product may be used.

[0038] In the present invention, from the viewpoint of the corrosion resistance of the coating film obtained, the water-based organic polymer compound (A) is preferably at least one selected from acrylic resins, polyurethane resins and epoxy resins, and particularly preferably acrylic resins and polyurethane resins.

[0039] When an acrylic resin is included, the content of the non-volatile content of the acrylic resin is preferably 20 parts by mass or more, and more preferably 50 parts by mass or more, based on 100 parts by mass of the total non-volatile content of the aqueous organic polymer compound (A).

[0040] In addition, when the aqueous organic polymer compound (A) contains an acrylic resin, at least one aqueous organic polymer compound selected from the aqueous organic polymer compounds (A) other than the acrylic resin may be used in combination with the acrylic resin. In this case, the amount of the other combined resin is preferably 80 parts by mass or less, more preferably 50 parts by mass or less, of the non-volatile content of the aqueous organic polymer compound (A) based on 100 parts by mass of the total non-volatile content of the aqueous organic polymer compound (A).

[0041] In this specification, the term "non-volatile content" refers to the residue remaining after removing volatile components such as water and organic solvents, and is the component that will form the coating film. For example, the drying conditions for the sample when measuring the mass of the non-volatile content include a method in which 1 gram of the sample is heated in a dryer at 110°C for 1 hour.

[0042] In the present invention, the aqueous organic polymer compound (A) is preferably contained in the metal surface treatment composition in an amount of 20 parts by mass or more, and more preferably 30 parts by mass or more, based on 100 parts by mass of the nonvolatile content of the metal surface treatment composition, from the viewpoints of storage stability in a paint state and corrosion resistance of the coating film. On the other hand, the aqueous organic polymer compound (A) is preferably contained in the metal surface treatment composition in an amount of 85 parts by mass or less, and more preferably 75 parts by mass or less, based on 100 parts by mass of the nonvolatile content of the metal surface treatment composition.

[0043] <Emulsifier (B)> The metal surface treatment composition of the present invention contains an emulsifier (B) containing at least one selected from an amphiphilic substance that forms closed vesicles and a polycondensation polymer having a hydroxyl group.

[0044] (Amphophilic substance that forms closed endoplasmic reticulum) In the present invention, the amphiphilic substance that forms a closed endoplasmic reticulum (vesicle) is not particularly limited, but examples thereof include derivatives of polyoxyethylene hydrogenated castor oil represented by the following general formula 1, or dialkylammonium derivatives, trialkylammonium derivatives, tetraalkylammonium derivatives, dialkenylammonium derivatives, trialkenylammonium derivatives, or halogen salt derivatives of tetraalkenylammonium derivatives represented by the following general formula 2.

[0045] General formula 1

[0046] [ka]

[0047] In general formula 1, E, which is the average number of moles of ethylene oxide added, is an integer of 3 to 200, and L, M, N, X, Y and Z are each an integer of 0 to 100.

[0048] General formula 2

[0049] [ka]

[0050] In general formula 2, R 1 and R 2 are each independently an alkyl or alkenyl group having 8 to 22 carbon atoms; R 3 and R 4 are each independently a hydrogen atom or an alkyl group having 1 to 4 carbon atoms; and X is F, Cl, Br or I.

[0051] As the amphiphilic substance, a derivative of polyoxyethylene hydrogenated castor oil can be preferably used.

[0052] When the emulsifier (B) to be blended is a derivative of polyoxyethylene hydrogenated castor oil, from the viewpoints of the storage stability of the metal surface treatment composition and the corrosion resistance and solvent resistance of the film obtained from the metal surface treatment composition, E in general formula 1 is preferably 20 or more, and more preferably 30 or more.

[0053] As the amphipathic substance, phospholipids or phospholipid derivatives, particularly those in which a hydrophobic group and a hydrophilic group are ester-bonded, may be used.

[0054] Examples of phospholipids include compounds represented by the following general formula 3. Among the compounds represented by general formula 3, DLPC (1,2-Dilauroyl-sn-glycero-3-phospho-rac-1-choline) with a carbon chain length of 12, DMPC (1,2-Dimyristoyl-sn-glycero-3-phospho-rac-1-choline) with a carbon chain length of 14, and DPPC (1,2-Dipalmitoyl-sn-glycero-3-phospho-rac-1-choline) with a carbon chain length of 16 are preferred.

[0055] General formula 3

[0056] [ka]

[0057] In the general formula 3, n is an integer of 11-17.

[0058] Furthermore, lecithin such as egg yolk lecithin or soybean lecithin may be used as the phospholipid.

[0059] In addition, fatty acid esters may be used as the amphiphilic substance. Examples of fatty acid esters that can be used include glycerin fatty acid esters (tetraglyceryl monostearate, decaglyceryl tristearate, etc.), sucrose fatty acid esters (sucrose stearate, etc.), sorbitan fatty acid esters, and propylene glycol fatty acid esters. Among these, glycerin fatty acid esters and sucrose fatty acid esters are particularly preferred.

[0060] (Polycondensation polymer having hydroxyl group) Moreover, examples of the polycondensation polymer having a hydroxyl group include a compound represented by general formula 4 in which a hydrophobic group has been introduced into some of the hydroxyl groups.

[0061] General formula 4

[0062] [ka]

[0063] In the general formula 4, each R is independently a hydrogen atom, a methyl group, or -[R'O] m H (wherein R' is an alkyl group and m is an integer of 1 or more), or -R''OC p H 2p+1(wherein R″ is an alkyl group having a hydroxyl group in the side chain, and p is an integer of 8 to 22), and n is an integer of 100 or more. If n is too small, stable particles are difficult to form, but in the present invention, a hydrophobic group is introduced to facilitate the formation of stable particles, so n can be a lower value than in the past. The specific value may be appropriately set, and may be, for example, 500 or more, 1000 or more, 1500 or more, or 2000 or more. R′ and R″ are merely groups used in synthesizing the emulsifier (B) and may be various, for example, R′ may be an alkyl group having about 1 to 3 carbon atoms, and R″ may be a hydroxypropyl group.

[0064] Specific examples of polycondensation polymers having hydroxyl groups include hydrophobized hydroxypropyl methylcellulose (e.g., stearoxy hydroxypropyl methylcellulose), and commercially available products such as the "Sangelose" (registered trademark) series ("60L", "90L", "60M", "90M", etc.) manufactured by Daido Chemical Industry Co., Ltd. can also be used.

[0065] From the viewpoint of storage stability, the blending ratio of the emulsifier (B) is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, based on 100 parts by mass of the nonvolatile content of the aqueous organic polymer compound (A). On the other hand, the content of the emulsifier (B) is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, based on 100 parts by mass of the nonvolatile content of the aqueous organic polymer compound (A).

[0066] <Silane coupling agent (C)> The silane coupling agent, which is component (C) of the metal surface treatment composition of the present invention, improves the curability (particularly under low-temperature, short-time drying conditions) and the adhesion of the resulting coating to the substrate surface, and contributes to improving the corrosion resistance and solvent resistance of the coating.

[0067] Examples of the silane coupling agent (C) include N-β (aminoethyl) γ-aminopropyl trimethoxysilane, N-β (aminoethyl) γ-aminopropyl methyl dimethoxysilane, γ-methacryloxypropyl trimethoxysilane, N-β (N-vinylbenzylaminoethyl γ-aminopropyl trimethoxysilane hydrochloride, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl triethoxysilane, γ-glycidoxypropyl methyl dimethoxysilane, γ-glycidoxypropyl methyl diethoxysilane, γ-mercaptopropyl trimethoxysilane, γ-mercaptopropyl methyl dimethoxysilane, methyl trimethoxysilane, vinyl triacetoxysilane, γ-chloropropyl trimethoxysilane, hexamethyldisilazane, γ-anilinopropyl trimethoxysilane, vinyl trimethoxysilane, vinyl triethoxysilane, octadecyl dimethyl [3- (trimethoxysilyl) propyl] ammonium chloride, and trimethylchlorosilane. These may be contained alone or in combination of two or more kinds.

[0068] Among these, epoxy group-containing silane coupling agents such as γ-glycidoxypropyltrimethoxysilane and γ-glycidoxypropyltriethoxysilane are preferred from the standpoint of corrosion resistance, solvent resistance, and the like. Furthermore, amino group-containing silane coupling agents such as N-β(aminoethyl)γ-aminopropyltrimethoxysilane and N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane are suitable from the viewpoint of corrosion resistance.

[0069] The silane coupling agent (C) may be a hydrolysis condensation product. The hydrolysis condensation product of the silane coupling agent means an oligomer of the silane coupling agent obtained by hydrolysis condensation using the silane coupling agent as a raw material.

[0070] The amount of the silane coupling agent (C) is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and even more preferably 30 parts by mass or more, relative to 100 parts by mass of the nonvolatile content of the aqueous organic polymer compound (A), from the viewpoints of the curability of the metal surface treatment composition, the corrosion resistance and solvent resistance of the film obtained from the surface treatment composition, etc. On the other hand, the amount of the silane coupling agent (C) is preferably 420 parts by mass or less, more preferably 400 parts by mass or less, and even more preferably 230 parts by mass or less, relative to 100 parts by mass of the nonvolatile content of the aqueous organic polymer compound (A).

[0071] <Metal surface treatment composition> The metal surface treatment composition of the present invention contains the above-mentioned aqueous organic polymer compound (A), specific emulsifier (B) and silane coupling agent (C), and may further contain optional components other than these components, as necessary. Examples of other optional components include silica particles, lubricating agents, thickeners, anti-cisternling agents, defoamers, oxidizers, antibacterial agents, anti-rust agents (tannic acid, phytic acid, benzotriazole, etc.), pH adjusters (formic acid, acetic acid, etc.), phosphoric acid compounds (orthophosphoric acid, hydroxymethane diphosphonic acid, 1-hydroxyethane-1,1-diphosphonic acid (HEDP), etc.), vanadium salts (ammonium metavanadate, vanadyl sulfate, sodium metavanadate, etc.), fluorometallic acids and their salts (hydrofluoric zirconate, ammonium fluoric zirconate, hydrofluoric titanate, ammonium fluoric titanate, etc.), coloring pigments, extender pigments, conductive materials, hydrophilic solvents (methanol, ethanol, isopropyl alcohol, ethylene glycol-based solvents, propylene glycol-based solvents, etc.), and the like.

[0072] The lubricant imparts lubricity to the resulting coating, and is suitable for applications involving press molding, etc. Specific examples of the lubricant imparting agent include fluororesin fine powders (e.g., fine powders of tetrafluoroethylene resin, tetrafluoroethylene-hexafluoropropylene copolymer resin, tetrafluoroethylene-perfluoroalkylvinyl ether copolymer resin, tetrafluoroethylene-ethylene copolymer resin, trifluorochloroethylene resin, vinylidene fluoride resin, etc.), polyolefin wax (e.g., polyethylene wax, polypropylene wax, etc.), lubricants containing a mixture of polyolefin and fluororesin in one particle, graphite, boron nitride, carbon fluoride, etc.

[0073] The amount of the lubricant added is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, based on 100 parts by mass of the nonvolatile content of the aqueous organic polymer compound (A). On the other hand, the amount of the lubricant added is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, based on 100 parts by mass of the nonvolatile content of the aqueous organic polymer compound (A).

[0074] The metal surface treatment composition of the present invention described above has a non-volatile content of preferably 20% by mass or less, more preferably 15% by mass or less, from the viewpoint of storage stability, while the non-volatile content of the metal surface treatment composition is preferably 6% by mass or more, more preferably 10% by mass or more, from the viewpoint of coatability in order to ensure an adequate amount of the composition adhered to the metal surface.

[0075] The reason why the metal surface treatment composition of the present invention has excellent storage stability is not clear, but the present inventors believe it is as follows. The stabilizing phase of closed vesicle particles or polycondensation polymer particles, which are produced in advance or during the production stage of the metal surface treatment composition, is present at the interface between the aqueous phase and the aqueous organic polymer compound phase and forms an emulsified state via van der Waals forces, so that a good emulsified state can be formed regardless of the composition and conditions of the aqueous organic polymer compound phase and the aqueous phase. It is considered that such an emulsified state can effectively suppress not only the stability of the aqueous organic polymer compound phase itself but also the reaction between the aqueous organic polymer compound phase and the ionic compound contained in the aqueous phase.

[0076] In order to form such an emulsion-stabilized state in the present invention, a step of dispersing the amphiphilic substance in closed endoplasmic reticulum (forming vesicles) or a step of forming a polycondensation polymer having hydroxyl groups into particles is necessary. This step requires various measures depending on the materials used, but can be achieved by, for example, any one of or a combination of the steps of diluting the amphiphilic substance and / or the polycondensation polymer having hydroxyl groups with water, heating to a temperature above the melting point or softening point, adding a cleaving agent such as urea to break hydrogen bonds, and adjusting the pH to 5 or less.

[0077] <Method of manufacturing metal surface treatment composition> In the present invention, the above-mentioned water-based organic polymer compound (A) is emulsion-stabilized by the above-mentioned emulsifier (B) specified in the present invention.

[0078] A first method for producing a metal surface treatment composition includes a step of mixing a composition containing an aqueous organic polymer compound (A) with an emulsifier (B) containing at least one selected from an amphiphilic substance that forms closed vesicles and a polycondensation polymer having a hydroxyl group. A second method for producing a metal surface treatment composition includes a step of adding an emulsifier (B) containing at least one selected from an amphiphilic substance that forms closed vesicles and a polycondensation polymer having a hydroxyl group to a composition containing an aqueous organic polymer compound (A) under stirring.

[0079] The first and second production methods are suitable for the case where an amphiphilic substance that forms closed vesicles is used as the emulsifier (B). According to the first and second production methods, the aqueous organic polymer compound (A) can be emulsified and stabilized while producing or generating closed vesicles.

[0080] A third manufacturing method for manufacturing a metal surface treatment composition includes a step of adding an emulsifier (B) containing at least one selected from an amphiphilic substance forming closed vesicles and a polycondensation polymer having a hydroxyl group to water under stirring to obtain a water dilution of the emulsifier (B) (water dilution step), and a step of mixing a composition containing an aqueous organic polymer compound (A) with the water dilution (mixing step). A fourth manufacturing method includes a step of adding an emulsifier (B) containing at least one selected from an amphiphilic substance forming closed vesicles and a polycondensation polymer having a hydroxyl group to water under stirring to obtain a water dilution of the emulsifier (B) (water dilution step), and a step of adding the water dilution to a composition containing an aqueous organic polymer compound (A) under stirring (mixing step).

[0081] According to the third and fourth manufacturing methods, closed vesicles or polycondensation polymer particles having hydroxyl groups are produced in advance in the water dilution step, and these are mixed with the aqueous organic polymer compound (A), thereby improving the emulsion stabilization of the aqueous organic polymer compound (A) in the paint, and enabling the stable production of the metal surface treatment composition. In the third and fourth production methods, when an emulsifier made from a polycondensation polymer having a hydroxyl group is used as the emulsifier (B), an emulsifier obtained by the method described in Japanese Patent No. 5652920 can be suitably used.

[0082] The stirring speed when adding the emulsifier (B) or the water dilution of the emulsifier (B) to the aqueous organic polymer compound (A) is not particularly limited, and may be set at a speed at which the outer side of the vortex generated by stirring collides with the inner wall of the stirring vessel. By stirring at such a speed, the entire components can be mixed uniformly. Specifically, the stirring speed is preferably 200 to 4000 rpm, more preferably 500 to 3000 rpm.

[0083] The reaction temperature when mixing the aqueous organic polymer compound (A) with the emulsifier (B) or a water-diluted product of the emulsifier (B) is preferably 5 to 40°C, more preferably 10 to 30°C, from the viewpoint of the storage stability of the coating material.

[0084] The reaction time when mixing the aqueous organic polymer compound (A) with the emulsifier (B) or a water-diluted product of the emulsifier (B) is preferably 0.1 to 24 hours, more preferably 0.2 to 8 hours, from the viewpoint of the storage stability of the coating material.

[0085] The emulsifier (B) may be used after being heated to a temperature equal to or higher than its melting point or softening point.

[0086] <Metal surface treatment method> The metal surface treatment method of the present invention is a method of applying the metal surface treatment composition of the present invention onto a metal substrate and drying it, and is a method of forming a treatment film of the metal surface treatment composition of the present invention on the surface of the metal substrate. In the present invention, the "treatment film" includes not only a continuous treatment film, but also a treatment product that is not a continuous treatment film due to a small treatment adhesion amount and is discontinuous.

[0087] The metal substrate is not limited in any way so long as it is a metal material, and examples thereof include iron, copper, aluminum, tin, zinc, and alloys containing these metals, as well as plated steel sheets or vapor-deposited products made of these metals. Among these, metal sheets made of the above metals are preferably used.

[0088] Examples of metal sheets used as the metal substrate include cold-rolled steel sheets, hot-dip galvanized steel sheets, electrogalvanized steel sheets, zinc alloy (zinc-iron, zinc-aluminum, zinc-nickel, and other alloys)-plated steel sheets, aluminum-plated steel sheets, stainless steel sheets, copper-plated steel sheets, tin-plated steel sheets, aluminum sheets, copper sheets, etc. Among these, galvanized steel sheets (including both hot-dip galvanized steel sheets and electrogalvanized steel sheets) and zinc alloy-plated steel sheets are preferred.

[0089] Before applying the metal surface treatment composition of the present invention to the metal substrate, the metal substrate can be surface-conditioned by one or more of degreasing, pickling, washing with hot water, washing with detergent, etc. In any case, it is preferable to wash the metal substrate thoroughly with water at the end. The liquid temperature of the metal surface treatment composition of the present invention at the time of application may be room temperature, but it can be cooled or heated as desired.

[0090] The surface of the metal substrate may be provided with a first layer formed by other surface treatment. The first layer is formed for the purpose of strengthening the adhesion between the coating film formed by the metal surface treatment composition of the present invention and the metal surface, and is preferably formed by a chromium-free surface treatment agent.

[0091] The metal surface treatment composition of the present invention can be applied to the above-mentioned metal substrate by a known method such as roll coating, spray coating, brush coating, electrostatic coating, immersion, electrodeposition coating, curtain coating, roller coating, etc., after diluting with water or the like to a viscosity suitable for coating as necessary, and then drying to form a surface treatment film. The above-mentioned surface treatment film may be formed on only one side or both sides of the metal substrate.

[0092] The amount of the coating film formed by the metal surface treatment composition of the present invention is not particularly limited, but is usually 0.4 to 3.6 g / m 2 , preferably 0.5 to 2.5 g / m 2 From the viewpoints of corrosion resistance and workability, it is preferable that the range be within this range.

[0093] The drying conditions for the treatment film may be appropriately set, but when baking continuously a coating applied by a coil coating method or the like, it can usually be carried out by heating for 5 to 60 seconds under conditions where the maximum temperature reached by the material is 60 to 200° C., preferably 70 to 120° C. When baking in a batch system, it can also be carried out by heating for 1 to 30 minutes at an atmospheric temperature of 100 to 180° C.

[0094] <Surface-treated metal sheet> The surface-treated metal sheet of the present invention is a surface-treated metal sheet obtained by subjecting the surface of a metal substrate to a surface treatment with the metal surface treatment composition of the present invention. The surface-treated metal sheet of the present invention is obtained by subjecting a metal substrate to a plate-like shape and by the above-mentioned metal surface treatment method of the present invention.

[0095] The surface-treated metal sheet of the present invention has a coating weight of 0.4 to 3.6 g / m 2 , preferably 0.5 to 2.5 g / m 2 From the viewpoints of corrosion resistance and workability, it is preferable for the range to be within this range.

[0096] On the treatment film of the surface-treated metal sheet of the present invention, an upper layer film such as a colored coating film or a clear coating film can be further formed for the purpose of improving the cosmetic appearance, durability, and other functionality, etc. The formation of this upper layer film can be carried out before the surface-treated metal sheet of the present invention is molded, but is preferably carried out after the molding. EXAMPLES

[0097] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following examples, "parts" and "%" mean "parts by mass" and "% by mass", respectively.

[0098] [Synthesis Example 1: Synthesis of cationic acrylic resin] (Preparation of Aqueous Dispersion of Amino Group-Containing Acrylic Resin (A1)) A reaction vessel equipped with a thermometer, a thermostat, a stirring device, a reflux condenser, a nitrogen gas inlet tube and a dropping device was charged with 50 parts of propylene glycol (PG) monomethyl ether, stirred and mixed in a nitrogen stream, and heated to 105°C. Then, a mixture of 20 parts of styrene (St), 45 parts of methyl methacrylate (MMA), 5 parts of n-butyl acrylate (nBA), 5 parts of 2-hydroxyethyl acrylate (2-HEA) and 25 parts of 2-(N,N-dimethylamino)ethyl methacrylate (DMAEMA) and a mixture of 2 parts of tert-butyl peroxy-2-ethylhexanoate (PBO) and 15 parts of propylene glycol (PG) monomethyl ether were dropped at the same time over 3 hours, and the mixture was aged for 1 hour after the end of the dropwise addition. Thereafter, the mixture was diluted with propylene glycol monomethyl ether and mixed with stirring for 30 minutes to obtain an amino group-containing acrylic resin (S1) solution with a non-volatile content (NV value) of 45%.

[0099] Next, 111 parts of the amino group-containing acrylic resin (S1) solution having a non-volatile content of 45% was charged into a reaction vessel equipped with a thermometer, a thermostat, a stirring device, a reflux condenser, a nitrogen gas inlet tube, and a dropping device, and the mixture was stirred and mixed. The temperature was raised to 80°C, and the solvent was removed under reduced pressure until the non-volatile content reached 69%. Next, the mixture was cooled to 60° C., and 20 parts of styrene, 20 parts of methyl methacrylate, 7 parts of n-butyl acrylate, 2.5 parts of 2-hydroxyethyl methacrylate (2-HEMA), 0.5 parts of allyl methacrylate (AMA), and 3 parts of acetic acid were added to the reaction vessel and mixed with stirring for 15 minutes. Then, after cooling to 40° C., 180 parts of deionized water (DIW) was added dropwise over 1 hour, and after completion of the dropwise addition, the mixture was aged for 15 minutes. The temperature was then raised to 60°C, 0.3 parts of sodium ascorbate and 0.3 parts of a 5% aqueous solution of ferrous sulfate were added, and then a mixture of 0.4 parts of 30% aqueous hydrogen peroxide and 30 parts of deionized water was added dropwise over 1 hour, followed by maturing for 1 hour. This resulted in an aqueous dispersion of amino group-containing acrylic resin particles (A1) with a non-volatile content of 30% and a mean particle diameter of 75 nm [mean particle diameter measured at 23°C using a submicron particle size distribution analyzer "COULTER N5" (manufactured by Beckman Coulter)].

[0100] The resulting amino group-containing acrylic resin particles (A1) had an amine value of 45 mgKOH / g, a hydroxyl value of 23 mgKOH / g and a weight average molecular weight of 1,200,000.

[0101] (Manufacturing of work-in-progress D1) A vessel was charged with 333 parts of an aqueous dispersion of amino group-containing acrylic resin particles (A1) with a non-volatile content of 30% and 50 parts of an aqueous dispersion of emulsifier (B1) with a non-volatile content of 10%, and the mixture was thoroughly stirred to obtain a work in progress (D1). The aqueous dispersion of emulsifier (B1) was obtained by stirring 90 g of water with a disperser and adding 10 g of "NIKKOL HCO-10" (manufactured by Nikko Chemicals Co., Ltd., polyoxyethylene hydrogenated castor oil, E=10 in the above general formula 1) thereto with stirring.

[0102] (Work in progress D2~4) Work-in-progress products D2 to D4 were produced in the same manner as in the production of work-in-progress product D1, except that the materials used were changed according to the compositions shown in Table 1 in the production of work-in-progress product D1.

[0103] (Manufacturing of work-in-progress D5) A vessel was charged with 333 parts of an aqueous dispersion of amino group-containing acrylic resin particles (A1) with a nonvolatile concentration of 30%, and 5 parts of emulsifier (B5) were added while stirring with a disperser, followed by dilution with 45 g of water. The emulsifier (B5) used was "NIKKOL HCO-40" (manufactured by Nikko Chemicals Co., Ltd., polyoxyethylene hydrogenated castor oil, E=40 in the above general formula 1) which had been dissolved by storing in a constant temperature room at 50°C for 12 hours.

[0104] (Manufacturing of work-in-progress D6 to D34) Work-in-progress D6 to D34 were produced in the same manner as in the production of work-in-progress D1, except that the materials used were changed according to the compositions shown in Table 1. When the emulsifier was a solid at room temperature, the emulsifier was stored in a constant temperature room at 50°C for 12 hours and used in a dissolved state. Also, work in progress D28 was obtained by mixing 45 g of water with stirring 333 parts of the aqueous dispersion of amino group-containing acrylic resin particles (A1) having a non-volatile content of 30%.

[0105] In addition, the components of the water-based organic polymer compound (A), the emulsifier (B), and the emulsifiers other than the emulsifier (B) in Table 1 are as follows.

[0106] <Aqueous organic polymer compound (A)> A1: Amino group-containing acrylic resin (cationic acrylic resin synthesized in Synthesis Example 1 above (amino group-containing acrylic resin particle (A1) aqueous dispersion, non-volatile content 30%) A2: DIC Hydran CP-7520 (DIC Corporation, cationic polyurethane resin, non-volatile content 25%) A3: Adeka Bonditer HUX-841 (made by ADEKA Corporation, nonionic polyurethane resin, non-volatile content 32%) A4: Superflex 150 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., anionic polyurethane resin, non-volatile content 30%) A5: Modepics 302 (manufactured by Arakawa Chemical Industries, Ltd., anionic modified bisphenol A type epoxy resin, non-volatile content 33%)

[0107] <Emulsifier (B)> B1: Aqueous dispersion of NIKKOL HCO-10 (manufactured by Nikko Chemicals Co., Ltd., polyoxyethylene hydrogenated castor oil, E=10 in formula 1), non-volatile content of 10% B2: Aqueous dispersion of NIKKOL HCO-20 (manufactured by Nikko Chemicals Co., Ltd., polyoxyethylene hydrogenated castor oil, E=20 in formula 1), non-volatile content of 10% B3: Aqueous dispersion of NIKKOL HCO-30 (manufactured by Nikko Chemicals Co., Ltd., polyoxyethylene hydrogenated castor oil, E=30 in formula 1), non-volatile content of 10% B4: Aqueous dispersion of NIKKOL HCO-40 (manufactured by Nikko Chemicals Co., Ltd., polyoxyethylene hydrogenated castor oil, E=40 in general formula 1), non-volatile content of 10% B5: NIKKOL HCO-40 (manufactured by Nikko Chemicals Co., Ltd., polyoxyethylene hydrogenated castor oil, E=40 in general formula 1), undiluted B6: Aqueous dispersion of NIKKOL HCO-60 (manufactured by Nikko Chemicals Co., Ltd., polyoxyethylene hydrogenated castor oil, E=60 in general formula 1), non-volatile content of 10% B7: Aqueous dispersion of NIKKOL HCO-100 (manufactured by Nikko Chemicals Co., Ltd., polyoxyethylene hydrogenated castor oil, E=100 in general formula 1), non-volatile content 10% B8: Water dispersion of BLAUNON CW-40 (manufactured by Aoki Oil Industries Co., Ltd., polyoxyethylene hydrogenated castor oil, E=40 in general formula 1), non-volatile content 10% B9: Water dispersion of BLAUNON CW-200 (manufactured by Aoki Oil Industries Co., Ltd., polyoxyethylene hydrogenated castor oil, E=200 in general formula 1), non-volatile content 10% B10: Sangelose 90L (manufactured by Daido Chemical Industry Co., Ltd., aqueous dispersion of stearoxyhydroxypropyl methylcellulose, non-volatile content 0.5%)

[0108] <Emulsifiers other than emulsifier (B)> B11: Adeka Reasoap ER-20 (manufactured by ADEKA Corporation: polyoxyethylene-1-alkoxymethyl-2-(2-propenyloxy)ethyl ether, EO addition mole number 20) diluted with water, non-volatile content concentration 10% B12: Adeka Reasoap ER-40 (manufactured by ADEKA Corporation: polyoxyethylene-1-alkoxymethyl-2-(2-propenyloxy)ethyl ether, EO addition mole number 40) diluted with water, non-volatile content concentration 10% B13: Nonion LT-221 (NOF Corporation, polyoxyethylene sorbitan monolaurate) diluted in water, non-volatile content 10%

[0109] [Table 1]

[0110] [Examples 1 to 48, Comparative Examples 1 to 9] Each component was mixed according to the mixing ratio shown in Tables 2 to 7 below, deionized water was added to adjust the non-volatile content to 15 mass%, and acetic acid or formic acid was added appropriately to adjust the pH of the metal surface treatment composition to 4.5, followed by thorough stirring to obtain each metal surface treatment agent. The mixing amounts in Tables 2 to 7 below depend on the solid content mass or the active ingredient mass.

[0111] The components of the silane coupling agent (C) in Tables 2 to 7 are as follows.

[0112] <Silane coupling agent (C)> C1;KBM-402;Manufactured by Shin-Etsu Chemical Co., Ltd., γ-glycidoxypropylmethyldimethoxysilane, active ingredient 100% C2;KBM-403;Manufactured by Shin-Etsu Chemical Co., Ltd., γ-glycidoxypropyltrimethoxysilane, active ingredient 100% C3; KBE-402; Shin-Etsu Chemical Co., Ltd., γ-glycidoxypropylmethyldiethoxysilane, 100% active ingredient C4; KBE-403; Shin-Etsu Chemical Co., Ltd., γ-glycidoxypropyltriethoxysilane, 100% active ingredient C5;KBM-803;Manufactured by Shin-Etsu Chemical Co., Ltd., γ-mercaptopropyltrimethoxysilane, 100% active ingredient C6;KBM-602;Shin-Etsu Chemical Co., Ltd., N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, 100% active ingredient C7;KBM-603;Shin-Etsu Chemical Co., Ltd., N-β(aminoethyl)γ-aminopropyltrimethoxysilane, 100% active ingredient C8;KBM-903;Manufactured by Shin-Etsu Chemical Co., Ltd., γ-aminopropyltrimethoxysilane, 100% active ingredient C9; KBE-903; Shin-Etsu Chemical Co., Ltd., γ-aminopropyltriethoxysilane, 100% active ingredient C10;KBM-503;Manufactured by Shin-Etsu Chemical Co., Ltd., γ-methacryloxypropyltrimethoxysilane, active ingredient 100% C11;KBM-1003;Shin-Etsu Chemical Co., Ltd., vinyltrimethoxysilane, active ingredient 100% C12;KBM-13;Made by Shin-Etsu Chemical Co., Ltd., methyltrimethoxysilane, active ingredient 100%

[0113] The following evaluations were carried out on the metal surface treatment compositions of Examples 1 to 48 and Comparative Examples 1 to 9 prepared above. The results are shown in Tables 2 to 7.

[0114] [State of metal surface treatment composition (storage stability)] 200 g of the metal surface treatment compositions obtained in the Examples and Comparative Examples were placed in a 0.25 L polypropylene container, nitrogen was sealed inside, and the container was stored at 40°C for one week. The container was then returned to room temperature, and the state and viscosity change in the container were evaluated according to the following criteria. The practical level was rated as "◎" or "○". [Evaluation Criteria] ◎: No change in viscosity and no sediment 〇: Viscosity change and slight sedimentation, but returns to normal with stirring △: Viscosity change and sedimentation were observed, and the viscosity did not return to normal even after stirring. ×: Coagulation solidification XX: The composition solidified during preparation without storage.

[0115] [Ethanol rubbing resistance test] (Conditions for preparing surface-treated metal sheets) Plating weight is 20g / m on one side 2A double-sided electrogalvanized steel sheet having a thickness of 0.8 mm was degreased by spraying a 2% alkaline degreaser (manufactured by Japan C.B. Chemical Co., Ltd., product name "Chemicleaner 561B", equivalent to silicic acid No. 3) solution at a liquid temperature of 65°C for 60 seconds, and then washed with hot water at a liquid temperature of 50°C for 20 seconds and dried to obtain an alkaline degreased metal sheet. The surface treatment agents obtained in the examples and comparative examples were applied to the obtained alkaline degreased metal sheet using a bar coater until the dried film weight was 1.0 g / m 2 The metal plate was then dried by heating for 12 seconds so that the maximum temperature reached by the metal plate was 100° C., thereby obtaining each surface-treated metal plate.

[0116] (Test Method) Four layers of gauze were soaked in ethanol and rubbed back and forth 20 times against the treated surface of each surface-treated metal sheet with a load of 1 kg, and the appearance change of the treated surface was visually observed and evaluated according to the following criteria. The practical level was rated as "◎" or "○". [Evaluation Criteria] ◎: No change was observed ○: Slight rubbing marks were observed ×: Scraping marks were clearly observed

[0117] [Corrosion resistance test] (Conditions for preparing surface-treated metal sheets) Each surface-treated metal sheet was obtained under the same conditions and by the same method as in the above-mentioned ethanol rubbing resistance test.

[0118] (Test Method) Each surface-treated metal plate was cut to a width of 7 cm and a length of 15 cm to obtain a surface-treated metal test plate for corrosion resistance testing. The end faces and back faces of the obtained test plates were sealed, and a salt spray test (SST) according to JIS Z 2371 was conducted to measure the area of ​​rust on the treated surface according to the rating number method, and the time it took for the rating number to reach 9 was evaluated according to the following criteria. The practical level was rated as "A" or "B". [Evaluation Criteria] A: It took more than 48 hours for the rating number to reach 9. B: It took more than 24 hours but less than 48 hours for the rating number to reach 9. C: It took less than 24 hours for the rating number to reach 9.

[0119] [Table 2]

[0120] [Table 3]

[0121] [Table 4]

[0122] [Table 5]

[0123] [Table 6]

[0124] [Table 7]

[0125] The results in Tables 2 to 7 show that the films formed using the metal surface treatment compositions of Examples 1 to 48 all had excellent storage stability and corrosion resistance, as well as excellent hardening properties.

Claims

1. A metal surface treatment composition comprising an aqueous organic polymer compound (A), an emulsifier (B) containing at least one selected from an amphiphilic substance that forms closed vesicles and a polycondensation polymer having a hydroxyl group, and a silane coupling agent (C).

2. 2. The metal surface treatment composition according to claim 1, wherein the water-based organic polymer compound (A) has at least one group selected from the group consisting of a nonionic hydrophilic group and a cationic hydrophilic group.

3. 3. The metal surface treatment composition according to claim 1, wherein the aqueous organic polymer compound (A) is at least one selected from the group consisting of an acrylic resin, a polyurethane resin, and an epoxy resin.

4. 4. The metal surface treatment composition according to claim 1, wherein the amphiphilic substance is polyoxyethylene hydrogenated castor oil.

5. The metal surface treatment composition according to any one of claims 1 to 4, wherein the silane coupling agent (C) is at least one selected from the group consisting of epoxy group-containing silane coupling agents and amino group-containing silane coupling agents.

6. 6. The metal surface treatment composition according to claim 1, wherein the aqueous organic polymer compound (A) is emulsion-stabilized by the emulsifier (B).

7. A method for producing the metal surface treatment composition according to any one of claims 1 to 6, comprising the steps of: A method for producing a metal surface treatment composition, comprising the step of mixing a composition containing an aqueous organic polymer compound (A) with an emulsifier (B) containing at least one selected from an amphiphilic substance that forms closed vesicles and a polycondensation polymer having a hydroxyl group.

8. A method for producing the metal surface treatment composition according to any one of claims 1 to 6, comprising the steps of: A method for producing a metal surface treatment composition, comprising the step of adding, under stirring, an emulsifier (B) containing at least one selected from an amphiphilic substance that forms closed vesicles and a polycondensation polymer having a hydroxyl group to a composition containing an aqueous organic polymer compound (A).

9. A method for producing the metal surface treatment composition according to any one of claims 1 to 6, comprising the steps of: A step of adding an emulsifier (B) containing at least one selected from an amphiphilic substance that forms closed vesicles and a polycondensation polymer having a hydroxyl group to water under stirring to obtain a water dilution of the emulsifier (B); A method for producing a metal surface treatment composition, comprising the step of mixing a composition containing an aqueous organic polymer compound (A) with the water dilution.

10. A method for producing the metal surface treatment composition according to any one of claims 1 to 6, comprising the steps of: A step of adding an emulsifier (B) containing at least one selected from an amphiphilic substance that forms closed vesicles and a polycondensation polymer having a hydroxyl group to water under stirring to obtain a water dilution of the emulsifier (B); A method for producing a metal surface treatment composition, comprising the step of adding the water dilution under stirring to a composition containing an aqueous organic polymer compound (A).

11. A method for treating a metal surface, comprising applying the metal surface treatment composition according to any one of claims 1 to 6 onto a metal substrate and drying the composition.

12. A surface-treated metal sheet, which is obtained by subjecting the surface of a metal substrate to a surface treatment with the metal surface treatment composition according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Surface-treating agent and surface-treated epdm article

    JP1999043647A

  • Metallic surface treating agent, metallic surface treating method and surface treated metallic material

    JP2002030460A

  • Surface treated steel sheet having excellent white rust resistance

    JP2003105562A

  • Emulsifying dispersant, method for emulsification and dispersion using it, and emulsion

    JP2006239666A

  • Emulsifier, emulsified product, method for producing emulsifier, and raw material for producing emulsifier

    JP2013216607A